Implementasi Sistem Pemantauan Beban Listrik Real-Time Pada Instalasi Rumah Tangga Berbasis Internet of Things - Ibrahim, Muhammad Isa; Heru Abrianto; A. Darmawan Sidik (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Real-time monitoring of electricity consumption has become essential in modern times to support efficient energy management in household installations. This study aims to design and implement an Internet of Things (IoT)-based electrical load monitoring system that allows users to monitor electrical parameters such as voltage, current, and power in real time. The system utilizes NodeMCU V3 (ESP-12) as the main controller, PZEM-004T V3 sensor for current detection, and the Blynk IoT application for hardware integration. Data from the sensor is transmitted to a cloud server and can be accessed via mobile devices. Additionally, the system includes a notification feature to alert users when power consumption exceeds a predefined threshold, preventing potential hazards such as short circuits. Testing results indicate that the system demonstrates high accuracy in detecting electrical parameters and enhances user awareness of energy consumption patterns. This system enables households to manage energy more efficiently and serves as a practical solution to support the concept of smart homes.